The Knowledge Level of Pregnant Women About Oral and Dental Health During Pregnancy - Apri Adiari Manu; Christina Ngadilah; Merniwati Sherly Eluama; Yohana Safira Horo; Chinedu Okafor (Lembaga Publikasi Ilmiah Nusantara, 2023)
Pregnancy is a physiological process that causes changes in a woman's body followed by hormonal changes, which not only affect general health but also affect oral and dental health. The purpose of this study was to determine the level of knowledge of pregnant women about oral health during pregnancy. The method used is descriptive method with a total sample taken of 28 pregnant women. Data collection was carried out by giving questionnaires to respondents to answer the questions given. The level of knowledge of pregnant women in Tuak Daun Merah Village (TDM) includes good criteria (41%), moderate criteria (50%) and bad criteria (9%). The level of knowledge about how to brush the teeth of pregnant women in the TDM Village with good criteria (39%), moderate criteria (47%), bad criteria (14%) this is because there are still pregnant women who do not know the time, frequency and how to brush their teeth properly. good and right. The level of knowledge about the diet of pregnant women in TDM Village with good criteria (75%), moderate criteria (21%), bad criteria (4%). The highest knowledge is with good criteria, the reason is by watching television and reading on the internet so that respondents understand and answer questions about eating patterns correctly. The level of knowledge about dental health control for pregnant women in the TDM Village with good criteria (10%), moderate criteria (61%), bad criteria (29%) this is because respondents know the time of dental health control but have not routinely carried out dental health control to medical facility.